Costs of delivering COVID-19 vaccine in Botswana during the height of the pandemic: a retrospective study - Kelsey Vaughan; Onalenna T. Mokena; Goabaone Rankgoane-Pono; Moses Keetile; Ulla Kou Griffiths (BMC Health Services Research)
Abstract Background The development, distribution and delivery of COVID-19 vaccines following the outbreak of the global coronavirus pandemic in February 2020 is the largest global immunization action in history. To assist with planning and resource mobilization efforts, a global-level model was used to estimate expected COVID-19 vaccine delivery costs employing data from the literature on childhood and adult flu vaccine delivery. However, country-level studies were needed to validate these estimates, learn lessons for future pandemics, and plan for forthcoming COVID-19 vaccination of priority groups. Methods We tested several methodological innovations to estimate total costs and costs per dose of COVID-19 vaccine delivery in Botswana. Costs incurred by all government sectors, parastatals, donors, and non-governmental organizations were included. Both fiscal costs (financial outlays) and the value of selected, existing human resources and donated vaccines (economic costs) were included. Results Fiscal delivery costs of COVID-19 vaccination were estimated at US$49.8 million for a 13-month period, with over half accounting for newly hired human resources. Newly hired staff supported not just vaccine delivery, but also co-ordination and social mobilization efforts. The value of existing human resources deployed to support COVID-19 vaccination was US$36.6 million. Based on 2.6 million doses delivered, the fiscal and economic delivery cost per dose was US$19 and US$33, respectively. Vaccines were procured and donated at an average price per dose of US$13.46, increasing the economic cost per dose delivered to approximately US$47. Conclusions In Botswana, costs were substantially higher than modelled estimates for COVID-19 vaccine delivery and the costs of delivering routine childhood vaccines. This suggests that rolling out a new vaccine to an entire population in the middle of a pandemic requires additional financial investments beyond what has been typical for immunization services in the past.